THE EFFECT OF READINESS PREPARATION FOR NURSING PRACTICE ON STRESS AND PERCEIVED COMPETENCES FOR PEDIATRIC NURSING PRACTICE OF NURSING STUDENTS - Srichanchai, Jeerawan; Sridan, Wasun (Journal of MCU Nakhondhat, 2021)
The objectives of this article were: 1) to study perceived competences for pediatric nursing practice and 2) to compare the level of stress of nursing student before and after experiment. This quasi - experimental had sample which were 134 nursing students of Srimahasarakham Nursing College, 3rd year of academic in 2019. All subject received the readiness preparation of nursing practice for 1 week, 30 hours. The research instruments used for collecting data were questionnaire on stress in nursing practice as well as questionnaire on perceived competences for pediatric nursing practice, those have content validity index at 1.00 and 0.90, respectively. The reliability with Cronbach’s Alpha Coefficients showed acceptable value of 0.83 and 0.74, respectively. Data were analyzed using descriptive statistics and t - test. In this research, it was found that: 1) The mean score of stress of nursing students after experiment were significantly lower than before the experiment at < 0.001 level. 2) The perceived competences for pediatric nursing practice of nursing students was in middle level. ( = 69.72, S.D. = 8.31). As a result, the model of readiness preparation for nursing practice in ward, the teachers should find some method that could encourage nursing students to increase knowledges and nursing practice. In order to reduce stress and improve more confidence in nursing skills.